(untitled) (Bangladesh Journal of Medical Science, 2024)
Background The purpose of this study is to compare two different techniques of tonsillectomy, the ultrasonic scalpel, and the cold dissection tonsillectomy. In this study, the duration of the surgery, intraoperative blood loss, post-operative pain and post-operative hemorrhage rate will be compared. Material and Methods This is a randomized controlled study involving 72 patients within the age of 3-40 years old with history of recurrent tonsillitis or tonsillar hypertrophy with obstructive symptoms. The patients are randomized to have both tonsils removed either by cold dissection method or ultrasonic scalpel method. During the surgery, operative time and intra-operative blood loss will be documented. The post-operative pain score was documented by the patient using the visual analog pain score. Post-operative hemorrhage will also be documented if present. Results The data collected will be analysed statistically. The duration of surgery for ultrasonic scalpel tonsillectomy was significantly shorter (mean 14.11 minutes versus 29.09 minutes, p <0.001) and intra-operative bleeding was also significantly lower (mean 9.58 ml versus 87.57 ml, p <0.001). There were no significant mean differences of post-operative pain score between cold dissection and ultrasonic scalpel in first 6 hours up to day 6 of post-surgery. However, post-operative pain score for cold dissection tonsillectomy was significantly less on the 7th day of post-surgery. Conclusions There was no documented post-operative hemorrhage. Ultrasonic scalpel tonsillectomy is more superior compared to cold dissection tonsillectomy in terms of operative time and intra-operative blood loss, however there is no difference in the post-operative pain score. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1142-1148